ترجمة الوثائق التاريخية القانونية: النسخ كوسيلة لقراءة النصوص وتسهيل ترجمتها: Translation of legal historical documents: transcription as a way to read texts and help for translation - بن عودة, عديلة (Maalim, 2021)
Abstract: Legal translation in Algeria is known as a translation of a special type and which is specific to official translators Jinterpreters, but its broader concept is used by all users of legal texts such as translators of the official journal and translators employed by various government institutions. However, the official translator is the only translator authorized and empowered to formalize and authenticate most of the translated texts (whether legal or otherwise). Consequently, I will study a component that is not popular academically in the community of translators, namely the translation of historical legal texts, and I target by this designation, the texts spreading in Algeria before independence, that is - ie during the ّ !"!# ّ $% ر ّ ' ()*" ّ + : + -' . - ص و "0 ,+ ّ "0 12# 3"4 70 period of Ottoman rule and French colonization. These documents, which have their impact even today, represent those relating in particular to notarized real estate contracts and those issued by the courts of justice during the Ottoman domination and then by the native people’s courts during the French colonization